Challenges of globalization / edited by Bibek Debroy - Debroy, Bibek (ed.) (New Delhi, 1998)
Globalization throws up many challen ges. What does the word globalization mean and what are the challenges? Are the forces of globalization uniformly beneficial, or do they accentuate ine quitable development across countries, across the gender gap and across present and future generations? What do countries have to do to tap the opportunities that globalization brings? How does India fit into this? These are questions that have no easy answers. But if answers are to be sought, the authors of the fifteen papers in this book are the best people to provide them. Oktay Yenal, Deepak Nayyar, I. G. Patel, Mahbub ul Haq, Ismail Seregeldin, Godwin, O.P. Obasi, Krishna Ahooja-Patel, Rakesh Mohan, Padma Desai, Toyoo Gyohten, Satu P. Limaye, Gilbert Etienne, John Elliott, P.N. Dhar and C. K. Prahalad have some of the answers. This updated and re-edited collection of some of the Rajiv Gandhi Institute's papers will be of interest to anyone following the forces of globa lization and what it means for the world and for India.
Keywords: Economic development